Studying the effect of the liquid biogas digestate and mineral fertilizer and both of them on some vegetative growth characteristics of peanut (Arachis hypogaea L.) Dr. Omeima Nasser * Dr. Haitham Eid ** Tofek Othman - ناصر, أميمة; عيد, هيثم; عثمان, توفيق (Latakia University Journal -Biological Sciences Series, 2021)
The research was conducted in Zahed station for Water and Irrigation Research, during the season growth (2020). The aim of this research was studying the effect of using two types of fertilizer together, and each of them alone, on some of the vegetative growth characteristics of peanuts. The types of fertilizers used were: mineral fertilizer (MF), organic fertilizer (Liquid Biogas Digestate, BD), and a mixture of both (MX). The following characteristics were studied (plant height, Plant Leaf Area (PLA), Leaf Index Area (LIA), wet weight and dry weight). The experiment was designed in a Randomized Complete Blocks Design (RCBD), which were (7) treatments and each of them was repeated (3) times (3 replications). The treatments were distributed as follows: one MF treatment, three organic BD treatments (6, 8, 10) L / m2, and three MX; whereas MF was mixed with each level of BD. The results showed that; the treatment MX (mineral + 10 L/m2) -which had a maximum level of BD- was significantly superior to all other treatments in all of the studied characteristics, as the following values were (86.46 cm, 8422.8 cm2, 2.8, 604.32 g, 213.14 g). As for the organic treatments (BD), it was found that the treatment which containing the maximum amount of BD (10L/ m2) was significantly superior in all the studied characteristics over the other two treatments that contained (6, 8 L/ m2). While it was found that there was no statistically significant difference between the treatment which was contained the maximum amount of organic BD (10 L/ m2) and the treatment of mineral fertilizers for all the studied characteristics.